Respostas
respondido por:
21
Olá!
Conceito Envolvido: # Função Composta
Temos:
f(x) = x - 3
f[g(x)] = 3x - 4
g(x) = ?
Vamos descobrir a função g(x):
f[g(x)] = g(x) - 3
3x - 4 = g(x) - 3
g(x) = 3x - 4+3
g(x) = 3x - 1 <--
Portanto: g(3) = 3.3 - 1 = 9 - 1 = 8 <---
Espero ter ajudado! :)
Conceito Envolvido: # Função Composta
Temos:
f(x) = x - 3
f[g(x)] = 3x - 4
g(x) = ?
Vamos descobrir a função g(x):
f[g(x)] = g(x) - 3
3x - 4 = g(x) - 3
g(x) = 3x - 4+3
g(x) = 3x - 1 <--
Portanto: g(3) = 3.3 - 1 = 9 - 1 = 8 <---
Espero ter ajudado! :)
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás